Geometric multigrid for Darcy and Brinkman models of flows in highly heterogeneous porous media: a numerical study - Kanschat, Guido; Lazarov, Raytcho (Journal of computational and applied mathematics, 2017)
We apply geometric multigrid methods for the finite element approximation of flow problems governed by Darcy and Brinkman systems used in modeling highly heterogeneous porous media. The method is based on divergence-conforming discontinuous Galerkin methods and overlapping, patch based domain decomposition smoothers. We show in benchmark experiments that the method is robust with respect to mesh size and contrast of permeability for highly heterogeneous media.